Real‐Time Assessment of Mitochondrial Toxicity in HepG2 Cells Using the Seahorse Extracellular Flux Analyzer. Issue 3 (18th March 2021) - Espinosa, Jether Amos; Pohan, Grace; Arkin, Michelle R.; Markossian, Sarine
Abstract: The liver is the primary organ responsible for drug detoxification. Drug‐induced liver injury (DILI) is a leading cause of attrition during drug development and is one of the main reasons that drugs are withdrawn from the market. Hence, the prevention of DILI plays a central role in the overall drug‐discovery process. Most of the liver's energy supply comes in the form of adenosine triphosphate (ATP), which is largely generated by mitochondria. This article describes the evaluation of drug‐induced mitochondrial dysfunction using the Seahorse Extracellular Flux Analyzer (Agilent). The described protocols detail the accurate measurement of ATP production rate in HepG2 cells after exposure to a panel of potentially toxic compounds. This assay measures changes in extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) as indicators of glycolysis and mitochondrial respiration—the two major energy‐generating pathways in a cell. This assay provides a useful model to predict mitochondrial dysfunction‐mediated DILI. © 2021 Wiley Periodicals LLC. Basic Protocol : Measurement of cellular ECAR, OCR, and ATP production in live HepG2 cells Support Protocol 1 : Culturing and maintaining of HepG2 cells Support Protocol 2 : Determining optimal cell density per well